2018
DOI: 10.1155/2018/7189402
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices on Periodontal Health among Adults, Misungwi, Tanzania

Abstract: The level of knowledge and practices on periodontal health of 388 adults in Misungwi District, Tanzania, was assessed. Analysis included frequency distributions and the chi-square test at a p value of 0.05. Many more participants were males (n=197; 50.8%) and of younger age group (n=215; 55.4%) and having seven years of education (n=257; 66.2%). Higher number of participants reported owning a mobile phone (n=289; 74.5%) and a radio (n=298; 76.8%), while few (n=45; 11.6%) had their houses connected to electrici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Similar findings were reported by another study conducted in UAE, which also showed no effect of employment status on the level of OH knowledge scores (Abu-Gharbieh, Saddik, El-Faramawi, Hamidi, & Basheti, 2019). In addition to the profession, formal education was found to be positively correlated with knowledge about OH and PD, this has been highlighted in other published studies (Azodo & Omili, 2014;Nyorobi et al, 2018;Zavras, Vrahopoulos, Souliotis, Silvestros, & Vrotsos, 2002). Our findings suggested the presence of association between educational level and level of oral hygiene and PD knowledge, which is reflected by a significantly higher awareness, the same pattern, was reported by previous surveys (Macek et al, 2010;Márquez-Arrico et al, 2019;Nyorobi et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar findings were reported by another study conducted in UAE, which also showed no effect of employment status on the level of OH knowledge scores (Abu-Gharbieh, Saddik, El-Faramawi, Hamidi, & Basheti, 2019). In addition to the profession, formal education was found to be positively correlated with knowledge about OH and PD, this has been highlighted in other published studies (Azodo & Omili, 2014;Nyorobi et al, 2018;Zavras, Vrahopoulos, Souliotis, Silvestros, & Vrotsos, 2002). Our findings suggested the presence of association between educational level and level of oral hygiene and PD knowledge, which is reflected by a significantly higher awareness, the same pattern, was reported by previous surveys (Macek et al, 2010;Márquez-Arrico et al, 2019;Nyorobi et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…In addition to the profession, formal education was found to be positively correlated with knowledge about OH and PD, this has been highlighted in other published studies (Azodo & Omili, 2014;Nyorobi et al, 2018;Zavras, Vrahopoulos, Souliotis, Silvestros, & Vrotsos, 2002). Our findings suggested the presence of association between educational level and level of oral hygiene and PD knowledge, which is reflected by a significantly higher awareness, the same pattern, was reported by previous surveys (Macek et al, 2010;Márquez-Arrico et al, 2019;Nyorobi et al, 2018). Individuals with unfavorable habits such as smoking, that is known to cause deterioration of OH and systemic health, will potentially show lower concern about their levels of oral hygiene, this can be seen in the findings of the current study and has been clearly shown in a number of other studies(Abu-Gharbieh et al, 2019).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…22 In contrast, a positive relationship was observed with other independent variables such as gender and educational level. 17,[23][24][25][26] Indeed, fear is a protective feeling that arises when facing a life-threatening condition such as infectious diseases. 27 In this study, the respondents reported a fear of contracting COVID-19…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, confrontation with threats to life negatively affects the OH status, as demonstrated by a study on refugees from war zones despite their reasonable awareness of oral hygiene 22 . In contrast, a positive relationship was observed with other independent variables such as gender and educational level 17,23‐26 …”
Section: Discussionmentioning
confidence: 99%